AUTOMATIC CONTROL SYSTEM: AUTOMATIC WHEELCHAIR WITH INTUITIF SENSOR ELECTRONIC WHEEL DRIVE WITH ELECTROMYOGRAM DETECTION AND NAVIGATION - ST. Khaeratul Mukarramah; Ariani Amri; Muh. Abdillah (Jurnal Media Elektrik, 2024)
This research aims to address the needs of individuals with tetraplegia, with the expectation that it can contribute to the development of automatic control systems and provide insights for the fields of healthcare and education. The control system in the wheelchair reads muscle contractions via electrodes attached to the muscles. These electrodes serve as muscle sensors. The muscle sensor data, often referred to as EMG, is 10-bit. The EMG sensor in the wheelchair shows that the wheelchair's movement is detected as moving forward when the data value generated by the EMG sensor reaches the minimum threshold of 589. The wheelchair moves forward when the Y-axis value is positive and moves backward when the Y-axis value is negative. The wheelchair will turn right or left when the X-axis value is positive or negative, respectively. Thus, when the X value is 20 and the Y value is 20, the wheelchair will move forward and turn right. The data collected by the IMU sensor can be wirelessly transmitted to an IoT (Internet of Things)-based system. This data can then be monitored through a browser on a laptop or PC, as well as through a smartphone.